2015
DOI: 10.1007/s11032-015-0414-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and heterologous expression analysis of JrVTE1 gene from walnut (Juglans regia)

Abstract: Tocopherol cyclase (VTE1) plays a key role in promoting the production of γ-tocopherol and improving total tocopherol content in photosynthetic organisms. Walnut is an important source of tocopherols in the human diet, and γ-tocopherol is the major tocopherol compound in walnut kernels. In this study, a full-length cDNA of the VTE1 gene was isolated from walnut using RT-PCR and RACE, and designated as JrVTE1. The full-length cDNA of the JrVTE1 gene contained a 1353-bp open-reading frame encoding a 451-amino-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…One is to block the cell lumen to make it difficult for water to effectively defuse into the cell wall, so as to improve the dimensional stability and decay resistance of wood. The explored modification methods include filling wood cell lumen by physical or chemical means, such as physical filling with poly (glycidyl methacrylate) [27] or phenolic resin [28], physical or chemical filling with polyacrylic resin [29][30][31], or physical or chemical filling with inorganic silica compounds [32]. However, this strategy implies the use of large amounts of filler, resulting in high cost.…”
Section: Introductionmentioning
confidence: 99%
“…One is to block the cell lumen to make it difficult for water to effectively defuse into the cell wall, so as to improve the dimensional stability and decay resistance of wood. The explored modification methods include filling wood cell lumen by physical or chemical means, such as physical filling with poly (glycidyl methacrylate) [27] or phenolic resin [28], physical or chemical filling with polyacrylic resin [29][30][31], or physical or chemical filling with inorganic silica compounds [32]. However, this strategy implies the use of large amounts of filler, resulting in high cost.…”
Section: Introductionmentioning
confidence: 99%
“…In the rice population inferred to study abiotic stress resistance, it was only found at the candidate region for salt and alkali resistance QTLs (Khamis, et al 2015).OsTPP3 (LOC_ Os07g43160) was co-expressed in N2-2, N2-z and N3-3 mut, which has three conserved domains to form catalytic sites for this enzyme. According to tissue-speci c expression analysis, its expression level is signi cantly higher in vegetative owers and seeds under the drought and salt stress treatment, and its expression level was upregulated signi cantly during growth and development period induce the increase of Tre6P (Yang, et al 2018).…”
Section: Venn Diagram In N2/n3 Mut and The Volcano Plots Of Degs In N...mentioning
confidence: 99%
“…For example, the nonexpressor of pathogenesis-related 1 (NPR1) gene encodes a transcriptional regulator of pathogenesis-related (PR) protein genes as part of the salicylic acid-dependent systemically acquired resistance (SAR) pathway. Sweet orange trees (Citrus sinensus) overexpressing NPR1 under the control of the phloem-specific SUC2 promoter exhibited 155 enhanced resistance to huánglóngbìng (citrus greening disease), and up to 46% of the engineered plants remained disease-free for 2 years 78 . These findings highlight the importance of promoter selection in overexpression studies and indicate that NPR1 possesses a conserved role among tree fruit species in the response to pathogens.…”
Section: Pathogen and Pest Resistancementioning
confidence: 99%